Pengaruh ROA, DER, dan CR terhadap Harga Saham pada Perusahaan Sub Sektor Farmasi yang Terdaftar di Bursa Efek Indonesia Periode 2021-2024 - Tika Purwanti; Nur Aini; Utami Puji Lestari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to determine and analyze the effect of Return on Assets (ROA) on stock prices, determine and analyze the effect of Debt to Equity Ratio (DER) on stock prices, and determine and analyze the effect of Current Ratio (CR) on stock prices. The population in this study consists of data from Pharmaceutical Sub-Sector Companies listed on the Indonesia Stock Exchange from 2021 to 2024, with a total of 34 companies listed. The research was conducted using a sampling method, with the research sample covering the period from 2021 to 2024 using a time series approach, resulting in a total sample of 118 data points. Data analysis was conducted using multiple linear regression with the SPSS version 27 program. The results of the study can be concluded as follows: 1) Return on Assets (ROA) has a positive and significant effect on stock prices. 2) Debt to Equity Ratio (DER) has a positive but insignificant effect on stock prices. 3) Current Ratio (CR) has a negative and significant effect on stock prices.